KAJIAN MANAJEMEN LALU LINTAS PADA DAERAH BELAKANG PELABUHAN PERIKANAN PANTAI KOTA PROBOLINGGO - Noor Salim (RELASI : JURNAL EKONOMI, 2014)
Geographically, Probolinggo region is located in north sea is directly adjacent to the Madura Strait , therefore the majority of the population and live near the beach activities or fishing ports. In the development of this port functions not only as a fishing port alone but also as a tourist. And also right next to the harbor there are two factories industry. This condition makes the harbor behind the increased traffic and require special attention. On the other hand the supply of and space to develop roads in the area behind the port is very limited and also the large financing. Hence the need for the above studies regarding the management in the area behind the fishing port. Based on the research and analysis of data, it can be concluded that there are existing road geometric intersection of four bersignal not that close to the port gate. This road has a width of ±5m for segment Village Mayangan direction, ± 10m for the segment towards the port, ±7m for the segment towards the city and ±10m for the segment direction Pilang Village. This road is two -lane roads and two-way. For existing traffic DS value obtained is 0.29 which means that the intersection of four levels of service B. For traffic coming 5 year DS value obtained was 0.42 , which means the intersection of four has a level of service C, which has the properties - properties that: The current stable but the speed and movement of vehicles controlled by traffic volume higher, medium traffic density because of internal obstacles to increased traffic,and the driver has to choose the speed limitations, moving lane or precede. It should be in the form of traffic management improvements: HV vehicles passing through the city should not be necessary that an alternative path towards Situbondo, Widening of existing roads, and short and long term is to regulate traffic in a way that complements existing traffic signs, complementary means of adequate lighting, should be considered for long-term use of direct current, and the intersection is recommended to be made signalized intersection.